2020
DOI: 10.5194/aab-63-367-2020
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sire line, birth weight and sex on growth performance and carcass traits of crossbred pigs under standardized environmental conditions

Abstract: Abstract. A variety of available terminal sire lines makes the choice of terminal sire line complex for the pig producer. Higher birth weights are important for subsequent growth performance and selection for this trait is also necessary in sire lines. The aim was to investigate the effect of sire line, birth weight and gender on growth performance, carcass traits and meat quality. In total 3844 crossbred pigs from Camborough Pig Improvement Company (PIC) dams matched with either a Synthetic (A) or Piétrain (B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 59 publications
1
5
1
Order By: Relevance
“…Pigs weighing 100 kg had lower juiciness, softness, shear forces, and total palatability than pigs weighing more than 100 kg ( p < 0.01). However, we found no effect of pre-slaughter weight on water holding capacity in our study, which contradicts the report of Elbert [ 11 ], whose research indicated that the heavy weight (120 kg) group had a higher fat content and water holding capacity than the light weight (100 kg) and medium weight (110 kg) groups ( p < 0.05).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Pigs weighing 100 kg had lower juiciness, softness, shear forces, and total palatability than pigs weighing more than 100 kg ( p < 0.01). However, we found no effect of pre-slaughter weight on water holding capacity in our study, which contradicts the report of Elbert [ 11 ], whose research indicated that the heavy weight (120 kg) group had a higher fat content and water holding capacity than the light weight (100 kg) and medium weight (110 kg) groups ( p < 0.05).…”
Section: Discussioncontrasting
confidence: 99%
“…According to Cobanovic et al [ 9 ] and Czyak-Runowska et al [ 10 ], pigs weighing between 115 and 130 kg had less meat and a higher prevalence of pale, soft, and exudative and dark, hard, and dry meat when compared to equivalents with a lower pre-slaughter weight. According to Elbert [ 11 ], increasing slaughter weight is associated with increased sensory scores for flavor, juiciness, and acceptability ( p < 0.05). Similarly, Rice et al [ 12 ] showed that pork from carcasses weighing more than 125 kg received higher desirable ( p < 0.05) evaluations for appearance and intention to purchase than swine weighing 111 kg.…”
Section: Introductionmentioning
confidence: 99%
“…Ultrasound measurements serve additionally for carcass grading either using, for example, the AUTOFOM III technology [62] by combining a number of 16 2-MHZ ultrasound transducers (Figure 9) or the BioQscan® pork carcass grading system (Biotronics, Inc., Ames, Iowa, USA). The lean meat percentage (or intramuscular fat) originating from ultrasound (carcass grading) can be used as important offspring information for boar or sire line selection in (cross-)breeding programs [63].…”
Section: Results Of Linear Measurements On An Ultrasound (B-mode) Image At the Longissimus Muscle (Between 13th/14th Vertebrae) Of A Germmentioning
confidence: 99%
“…The difference between the sexes in individual live weight and average daily gain were not statistically significant, however, the barrows of all combinations were heavier on average and grew faster. Some studies found more pronounced differences between sexes of piglets in favour of barrows (Elbert et al, 2020), while some studies did not (Škorjanc et al, 2007).…”
Section: Discussionmentioning
confidence: 99%